Analysis of Working Postures with Musculoskeletal Disorders (Msds) Complaint of Tailors in Ulak Kerbau Baru Village, Ogan Ilir - Betty Andriani; Anita Camelia; H.A Fickry Faisya (Faculty of Public Health, Sriwijaya University, 2020)
Tailor isone ofthe professions that has MSDsrisk. It isbecause of theworking posture, such as sitting for a long time and repetitive movements. The purpose of thisstudy is to determinerelationshipbetweenworking postures and Musculoskeletal Disordes (MSDs) of Tailors in Ulak Kerbau Baru VillageOgan Ilir. This research was an cross-sectional and method of sampling in this study was using totalsampling with sample were 75 respondents. Rapid Entire Body Assessment (REBA) method was used assessed the risk of workingposture and questionnaires. Nordic Body Map was used determine of Musculoskeletal Disorders. The data is performed using univariate and bivariate with chi-square.Based on calculations used the REBA posture tailor working 42.7% of respondents has high risk and 57.3% has medium risk. Results of this analysis used statistical there were a significant relationship between age (p-value = 0.006 CI 1,730-25,281), working period (p-value = 0.023 CI 1,343-30,271), working posture (pvalue 0.027 CI 1,284-11,847), and the working time (p-value = 0.032 CI 1,145-74,602) with Musculoskeletal Disorders (MSDs), and there was no significant relationhips between the sexes (p-value = 0.610 CI 0,224-1,898) with Musculoskeletal Disorders (MSDs).The majority of tailor work posture were at high risk, the researcher suggests to do intervention on modified factors, which are working postures and working time. Intervention can be done by using ergonomic work chair and make time to do stretch up (physical activity) every 30 minutes to reduce muscle fatigue.